Dissolved organic matter stimulates N2 fixation and nifH gene expression in Trichodesmium. Issue 4 (21st February 2020) - Benavides, Mar; Duhamel, Solange; Van Wambeke, France; Shoemaker, Katyanne M; Moisander, Pia H; Salamon, Ellen; Riemann, Lasse; Bonnet, Sophie
ABSTRACT: Mixotrophy, the combination of heterotrophic and autotrophic nutrition modes, is emerging as the rule rather than the exception in marine photosynthetic plankton. Trichodesmium, a prominent diazotroph ubiquitous in the (sub)tropical oceans, is generally considered to obtain energy via autotrophy. While the ability of Trichodesmium to use dissolved organic phosphorus when deprived of inorganic phosphorus sources is well known, the extent to which this important cyanobacterium may benefit from other dissolved organic matter (DOM) resources is unknown. Here we provide evidence of carbon-, nitrogen- and phosphorus-rich DOM molecules enhancing N2 fixation rates and nifH gene expression in natural Trichodesmium colonies collected at two stations in the western tropical South Pacific. Sampling at a third station located in the oligotrophic South Pacific Gyre revealed no Trichodesmium but showed presence of UCYN-B, although no nifH expression was detected. Our results suggest that Trichodesmium behaves mixotrophically in response to certain environmental conditions, providing them with metabolic plasticity and adding up to the view that mixotrophy is widespread among marine microbes. Abstract : Trichodesmium is generally considered an autotroph. This work shows an enhancement in N2 fixation and nifH gene expression in Trichodesmium as a response to dissolved organic matter compounds, indicating a mixotrophic potential.